Research and Development of a Nutrition Health Promotion Program for Preschool Children Based on Pender’s Health Promotion Model - Choojan , Saowanee; Ridthplake, Sirikanya; Deeaom, Akaradej; Yupa, Pacharin; Kantawan, Pantamanas (Journal of The Royal Thai Army Nurses, 2026)
This study employed a research and development design to develop a nutrition health promotion program for preschool children, based on Pender’s Health Promotion Model. The participants consisted of 32 parents of preschool children and 11 childcare teachers from an early childhood education center in Mueang District, Nakhon Ratchasima Province. The research instruments included a nutrition health promotion program for preschool children, a questionnaire assessing parents’ and teachers’ perceptions of nutritional practices, and a satisfaction assessment form for parents and teachers. Quantitative data were analyzed using descriptive statistics and paired t-tests. The developed program comprised 7 activities, covering nutritional status assessment, goal setting, fostering positive thinking and confidence in behavioral change, smart food selection activities, and promoting healthy nutrition for age-appropriate growth. The results indicated that after implementing the preschool nutrition health promotion program, parents and teachers demonstrated significantly improved perceptions of nutritional practices for preschool children (p < 0.05).